Developmental control of convergent floral pigmentation across evolutionary timescales. Issue 11 (17th July 2019) - Larter, Maximilian; Dunbar‐Wallis, Amy; Berardi, Andrea E.; Smith, Stacey D.
Abstract: Background: Convergent phenotypic evolution has been widely documented across timescales, from populations, to species, to major lineages. The extent to which convergent phenotypes arise from convergent genetic and developmental mechanisms remains an open question, although studies to‐date reveal examples of both similar and different underlying mechanisms. This variation likely relates to a range of factors, including the genetic architecture of the trait and selective filtering of mutations over time. Here we focus on floral pigmentation, and examine the degree of developmental convergence between white‐flowered lineages and white morphs within pigmented species. Results: Using the model clade Iochrominae, we find that white morphs and white‐flowered species are biochemically convergent, sharing an absence of colorful anthocyanin pigments. Regression analyses suggest that the expression levels of upstream genes are the strongest drivers of total pigmentation across species, although white species also show sharp down‐regulation of the downstream genes. The white morphs do not share this pattern and present overall expression profiles more similar to the pigmented species. Conclusions: These results suggest that the mechanisms underlying variation within populations differ from those which give rise to fixed differences between species. Future work will aim to uncover the genetic changes responsible for this developmental non‐convergence. Key Findings: Different genetic and developmental mechanisms can underlie convergent phenotypic evolution at different timescales. We describe convergent losses of floral anthocyanin pigments within and among species. Gene expression changes are responsible for losses at the species level, with a distinct developmental mechanism in the white morphs within species.